2017
DOI: 10.15760/trec.158
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Electric Bike Pilot Project at Three Employment Campuses in Portland, Oregon

Abstract: 13. Type of Report and Period Covered 14. Sponsoring Agency Code 15. Supplementary Notes AbstractThis report examines the results of an electric bike (e-bike) pilot project, which took place April 2014-September 2015 in the Portland region. Participants from three Kaiser Permanente Northwest campuses (1 urban and 2 suburban) were issued an e-bike for 10 weeks to use for various trip purposes, focusing on first/last-mile commuting. Participants were asked to complete three surveys-before, during and after using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…Accessibility: E-bike and e-scooter generally increase accessibility by enabling users to reach more distant locations that were beyond walking distance and poorly connected by public transport (MacArthur et al, 2017;Smith & Schwieterman, 2018). It is found that in Chicago e-scooters can make 16% more jobs accessible within 30 min of commuting time, although the impact is vastly different across the entire study area.…”
Section: Impact Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessibility: E-bike and e-scooter generally increase accessibility by enabling users to reach more distant locations that were beyond walking distance and poorly connected by public transport (MacArthur et al, 2017;Smith & Schwieterman, 2018). It is found that in Chicago e-scooters can make 16% more jobs accessible within 30 min of commuting time, although the impact is vastly different across the entire study area.…”
Section: Impact Estimationmentioning
confidence: 99%
“…Equity: Both e-bike and e-scooter sharing services are found to have the potential in expanding accessibility for regions and groups which are underserved by traditional modes (MacArthur et al, 2017;PBOT, 2019). There has been evidence showing that micromobility users are different from the typical early adopter profile in traditionally underserved regions (Shaheen & Cohen, 2019).…”
Section: Impact Estimationmentioning
confidence: 99%
“…Many individuals face physical limitations that may deter them from bicycling, such as health conditions, living in a hilly area, and living far from where they work and play. Studies have found that electric bicycles (e-bikes) can be useful for mitigating the effect of these barriers (MacArthur et al, 2017;Langford et al, 2013;. E-bikes provide a unique opportunity to enhance the development of connected bicycles because they come equipped with a battery, which can serve as a platform for integrating sensor technologies and GPS.…”
Section: Physical Applicationsmentioning
confidence: 99%
“…Studies have shown that the need to haul cargo and transport children can be a significant barrier to traveling by bicycle (MacArthur et al, 2017). Similar to the physical barriers, the electric assist of e-bikes could enhance the feasibility of bicycling for individuals who must carry additional weight they might not feel comfortable carrying on a standard bicycle, especially with connected features such as "No-Sweat Mode.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Although e-bike incentive programs have increased in recent years, to date there has been limited evaluation of program impacts on e-bike adoption or usage (McQueen, MacArthur, and Cherry 2019). Several studies in northern Europe and the US have found positive perception and behavior changes from interventions in the form of short-term e-bike loans of 1-10 weeks (Fyhri et al 2017;MacArthur et al 2017;Moser, Blumer, and Hille 2018;Wikstrøm and Böcker 2020). Moser, Blumer, and Hille (2018) reported that a two-week loan program 'had a long-term effect on participants' habitual associations with car use, regardless of whether they would go on to purchase an e-bike' after the intervention.…”
Section: Introductionmentioning
confidence: 99%